P 91 Characterization of amygdala enlargement in patients with mesial temporal lobe epilepsy by MRI volumetry. (May 2022) - Kirscht, A.; Zöllner, J.P.; Neuhaus, E.; Belke, M.; Knake, S.; Hattingen, E.; Rosenow, F.; Strzelczyk, A.
Abstract : Question: Amygdala enlargement (AE) can be a cause of mesial temporal lobe epilepsy (mTLE). Clinical characteristics of AE and pathophysiological relationship between AE and mTLE are not fully understood. In this study, patients with AE and mTLE were examined clinically and by magnetic resonance imaging (MRI) to describe this form of epilepsy in more detail. Methods: We retrospectively included patients examined in inpatient video-EEG monitoring with AE confirmed by neuroradiologists based on MRI. We determined amygdala size by autoamated volumetry of 3D T1-weighted images in the software freesurfer (v7.1.1) using amygdala size as a surrogate parameter for amygdala pathology. We compared the results of normalized volumetry of subcortical structures with those of a healthy control group, and correlated the volumes with various clinical parameters. Results: Of 52 patients (50% female, age 15-66 years), 38 (73.1%) showed a seizure onset zone concordant to the side of the AE. The most common seizure patterns were dialeptic (90.4%) and automotor (88.5%) seizures. Auras occurred in 65.4%, mainly psychic (30.8%), epigastric (23.1%), and gustatory auras (11.5%). A total of 88.5% of patients were drug refractory; of these, 13 underwent epilepsy surgery and 7 (53.8%) achieved complete seizure freedom (Engel 1A). On histology, the cause of AE was found to be tumor in 3 patients, focal cortical dysplasia (FCD) in 5 patients, and gliosis in 2. An autoimmune inflammatory pathology could be reliably determined in only 3 patients (5.8%). In 30 of 52 patients, automatic volumetry showed a significant enlargement of an amygdala (Z-score >1.96) compared to the normal cohort (N=175). Volumetrically determined AE was concordant to the radiologically diagnosed side in 80%. This group showed a mean amygdala volume of 2151mm 3 on the left side (range 1799-2515mm 3 ) and 2293mm 3 on the right side (range 2000-2560mm 3 ) compared to the normal cohort (mean 1773mm 3 left and 1909mm 3 right side, respectively). There was no significant correlation of amygdala size with epilepsy duration (p=0.4) and no significant clinical differences between purely radiologically and additionally volumetrically detected AE. Conclusions: Temporal lobe epilepsies due to AE have predominantly similar clinical characteristics despite heterogeneous etiopathogenesis. Automatic volumetry of AE does not detect all visually abnormal findings.